1964
DOI: 10.1021/i260011a014
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Carbon Vapor with Hydrogen and with Methane in a High Intensity Arc

Abstract: The financial support from the Avco Corporation is gratefully acknowledged for making possible the construction of the experimental apparatus and especially the sampling probes used in this study at high temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…The plasma formed consists, in the homogeneous phase (the one we are interested in here), of the polymeric forms of carbon vapor C1, C2, and C3, of atomic and molecular hydrogen, as well as of a number of radicals and molecules. However, reference to the work of Baddour and Blanchet (1,5) leads to the conclusion that for the conditions of the present study (atmospheric pressure; C/H2 ----0.75), acetylene is nearly maximum at 320,0~ its concentration being about two times higher than C2H. 2 and 3 related to propane flow rates of 0.3 X 10 -2 g-moles/rain and 1.2 X 10 :-2 g-moles/rain, it is observed that the maximum acetylene yields occur, as an average, at 3200 ~ and 4200~ when, respectively, 5 • 10 -4 and 19 X 10 .-4 g-motes/ rain iron vapor are injected into the reacting medium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The plasma formed consists, in the homogeneous phase (the one we are interested in here), of the polymeric forms of carbon vapor C1, C2, and C3, of atomic and molecular hydrogen, as well as of a number of radicals and molecules. However, reference to the work of Baddour and Blanchet (1,5) leads to the conclusion that for the conditions of the present study (atmospheric pressure; C/H2 ----0.75), acetylene is nearly maximum at 320,0~ its concentration being about two times higher than C2H. 2 and 3 related to propane flow rates of 0.3 X 10 -2 g-moles/rain and 1.2 X 10 :-2 g-moles/rain, it is observed that the maximum acetylene yields occur, as an average, at 3200 ~ and 4200~ when, respectively, 5 • 10 -4 and 19 X 10 .-4 g-motes/ rain iron vapor are injected into the reacting medium.…”
Section: Discussionmentioning
confidence: 99%
“…Since the refractory tips already mentioned provide conditions of homogeneous region within the considered reactor volume S, the following relation can be written moles C2H2 moles C2H 2 [1] moles C2H~ + moles Hg_ --mole C~Hs 4 a value of 1.5 for this ratio being equivalent to 100% C2H2 yield for the reaction 2CsHs----> 3C2H2 + 5H2 [2] where the acetylene and hydrogen concentrations are obtained from a sample analysis for a given test, the total content of hydrogen being used for the determination of the initial amount of propane. The samples are analyzed for acetylene and H2 which are, for all practical purposes, the only gas constituents found in all cases as products of reaction.…”
Section: Apparatus and Mode Of Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…Plooster and Reed [38] found good agreement between experimental and thermodynamic equilibrium concentrations of acetylene in a carbon tube. Baddour and Blanchet [39] used the thermodynamic equilibrium analysis to predict the maximum acetylene concentration and found which was obtained at the temperature of 3000°C. Dai [40] and Xie [41] acknowledged that the condition of gas-solid heterogeneous equilibrium should be taken into account to be more appropriate for analyzing the process of coal pyrolysis.…”
Section: Cleaner Production Of Acetylene By Coal Pyrolysis In Thermalmentioning
confidence: 99%